Vasoactive Agents for the Management of Variceal Bleeding: A Mixed Treatment Comparison Network Meta-analysis and Trial Sequential Analysis of Randomized Clinical Trials - Sridharan, Kannan; Sivaramakrishnan, Gowri (Drug Research, 2019)
Background Vasoactives such as terlipressin, somatostatin, vasopressin, octreotide and nitrates are commonly used to treat variceal bleeding. The present study is a network meta-analysis comparing the efficacy and safety of the above vasoactive agents for treating variceal bleeding.Methods Electronic databases were searched for appropriate randomized clinical trials evaluating vasoactives in cirrhotic patients with variceal bleeding. Random-effects model was used to generate the pooled estimates. Mortality was the primary outcome and bleeding control, re-bleeding rate, hospital stay, blood transfusion requirements and adverse events were the secondary outcome measures.Results Fifty randomized clinical trials were included of which 37 were included for the primary outcome. The overall analysis did not reveal any significant difference in the mortality risk between any of the vaso-active drugs except for terlipressin that had statistically significant benefits from direct pooled estimates. Somatostatin and terlipressin showed significant reduction in the mortality risks at 24 h. Terlipressin significantly reduced re-bleeding rate; somatostatin and vasopressin were associated with better hemostasis; and terlipressin and vasopressin significantly reduced the requirement for blood transfusion. Terlipressin, vasopressin and glyceryltrinitrate/vasopressin were also associated with increased risk of adverse events.Conclusion Terlipressin could be the best agent in the vasoconstrictor category for managing variceal bleeding. Somatostatin and vasopressin can serve as alternatives.
Keywords: terlipressin; somatostatin; vasopressin; octreotide; nitrates